Infraestructura del hardware para el sistema de registro de pacientes (PRAS) en el Hospital Nicolas Coto Infante. - Mosquera Holguín, Jorge Joel (2022)
Currently, information technologies are present in most companies or institutions since they provide innumerable benefits such as the automation of most functions that are performed manually, which significantly reduces costs, time and unnecessary work. The theme of this case study is "Hardware infrastructure for the patient registration system (PRAS) at the Nicolas Cotto Infante Hospital in the city of Vinces" whose objective is to analyze, identify and examine the different components of the infrastructure that it has. implemented the institution in search of problems when executing the patient registration system that speeds up the process of entry, exit and scheduling of patients of the hospital institution. Medical care is of vital importance and that is why these health institutions choose to implement infrastructures and software that allow basic processes to be automated and thus be able to provide more efficient and rapid care, for this reason it is essential to keep them in optimal conditions using different tools and methods such as They are periodic examinations of systems and infrastructure analysis in order to identify problems and solve them.